Comparison study of photocatalytic activity of titanium-rich materials derived from natural minerals ores using acidic leaching - Kansaard, Thanaphon; Phoohinkong, Weerachon; Mekprasart, Wanichaya; Sanguanpak, Samanya; Wannakon, Anucha; Pecharapa, Wisanu (My University, 2017)
Over past decades, titanium dioxide-based materials have been recognized as effectively practical photocatalysts for purification of toxicity waste. However, pure TiO2 photocatalyst is highly active under ultraviolet illumination. In this work, the effort has been focused on the synthesis of titanium-rich materials starting from minerals ores ilmenite ores and leucoxene ores by ball-milling process in combined with hydrochloric acid leaching method with optimized conditions. Crystallinity and morphologies of as-prepared samples were characterized by X-rays diffraction technique and scanning electron microscope. The photocatalytic activities of both derived-materials were studied and compared by degradation of Rhodamine B organic dye as organic toxicity compound under ultraviolet light and visible light. The results illustrate that the leucoxene-derived sample exhibits superior catalytic performance to the sample derived from ilmenite ores due to the greater Ti-content of the starting leucoxene ores.
Keywords: Acid Leaching and Rhodamine B; Photocatalyst; Titanium-rich materials